2015
DOI: 10.1371/journal.pone.0118475
|View full text |Cite
|
Sign up to set email alerts
|

GSK3β Inhibition Promotes Synaptogenesis in Drosophila and Mammalian Neurons

Abstract: The PI3K-dependent activation of AKT results in the inhibition of GSK3β in most signaling pathways. These kinases regulate multiple neuronal processes including the control of synapse number as shown for Drosophila and rodents. Alzheimer disease’s patients exhibit high levels of circulating GSK3β and, consequently, pharmacological strategies based on GSK3β antagonists have been designed. The approach, however, has yielded inconclusive results so far. Here, we carried out a comparative study in Drosophila and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 75 publications
1
37
1
Order By: Relevance
“…The important decrease in GSK3β expression levels and phosphorylation states between juvenile and adolescent/adult brains, presented here and in previous studies (Leroy et al ., ; Beurel et al ., ), may support this hypothesis. It has recently been demonstrated that GSK3β inhibition exhibits an age‐dependent effect on mammalian synaptogenesis (Cuesto et al ., ). GSK3β inhibition can repress/enhance synaptic formation depending on the age of the cultured neurons, suggesting that in young neurons, the mechanisms controlled by GSK3β differ from mature neurons.…”
Section: Discussionmentioning
confidence: 97%
“…The important decrease in GSK3β expression levels and phosphorylation states between juvenile and adolescent/adult brains, presented here and in previous studies (Leroy et al ., ; Beurel et al ., ), may support this hypothesis. It has recently been demonstrated that GSK3β inhibition exhibits an age‐dependent effect on mammalian synaptogenesis (Cuesto et al ., ). GSK3β inhibition can repress/enhance synaptic formation depending on the age of the cultured neurons, suggesting that in young neurons, the mechanisms controlled by GSK3β differ from mature neurons.…”
Section: Discussionmentioning
confidence: 97%
“…This might be related to the BDNF-dependent GSK3β activity reduction. The Ser9 of GSK3β is highly phosphorylated upon stimulation of synaptogenesis, and the inhibition of the kinase is required for dendritic growth and arborization, whereas an increase in its activity leads to marked shrinkage of dendrites [94,95]. Moreover, in vivo overexpression of GSK3β reduces neurogenesis in adult hippocampus [96] and induces pro-depressant-like events [97].…”
Section: Bdnf-regulated Action Of Gsk3βmentioning
confidence: 99%
“…Aβ42 oligomers where added to the cell culture 72 h after cell seeding (48 h after differentiation), at 3 different concentrations (Kayed and Glabe, 2006). To stimulate PI3K activity we used the peptide PTD4-PI3KAc, previously proved to trigger PI3K activation both in vitro and in vivo (Cuesto et al, 2015(Cuesto et al, , 2011Enriquez-Barreto et al, 2014). PTD4-PI3KAc was administered at 3 different time points, before Aβ42 (pretreatment), simultaneously with Aβ42 (co-treatment) or after Aβ42 addition (posttreatment) (Fig.…”
Section: Pi3k Extends Cell Survival Of Human Neurons Exposed To Aβ42 mentioning
confidence: 99%
“…Furthermore, pharmacological administration of a PTEN membrane-permeable peptide, unable to interact with Aβ42, rescues synapse deterioration (Knafo et al, 2016). Other PI3K regulators, like the signaling inhibitor GSK3-β, are known to elicit anti-synaptogenic actions in Drosophila and mice (Cuesto et al, 2015;Martín-Peña et al, 2006), with concomitant effects in LTP and long-term memory (Hooper et al, 2008). In addition, Jun kinase/AP-1 and Wnt signaling are also members of the synaptogenic pathway, as they are regulated by GSK3-β (Franciscovich et al, 2008).…”
Section: Pi3k Mechanisms In Aβ42-induced Synapse Toxicitymentioning
confidence: 99%
See 1 more Smart Citation